TEKNIK STORYTELLING DENGAN MEDIA WAYANG SEBAGAI UPAYA MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS V SEKOLAH DASAR - Kusumawati, Eli; Utami, Sri; Susanto, Natal Hari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the low level of student learning activity, so there is a need for action that can increase student learning activity. By using storytelling techniques and adding puppets, students are interested and enthusiastic about being active in the learning process. This research aims to increase students' active learning using storytelling techniques using wayang media. The subjects in this research were class V students with a total of 14 students. The data collection tool used was an observation sheet. The results of the research showed that the average pre-action student activity was 48.1% only in the fair category, in cycle I it increased to 64.29% in the good category and in cycle II it increased significantly to 87.14% in the very good category.